Rest stops during road transport: Impacts on performance and acute-phase protein responses of feeder cattle - Cooke, Reinaldo Fernandes [UNESP]; Guarnieri Filho, T. A. [UNESP]; Cappellozza, B. I.; Bohnert, D. W. (Amer Soc Animal Science, 2013)
Angus x Hereford steers (n = 42) and heifers (n = 21) were ranked by gender and BW on d 0 of the experiment and randomly assigned to 1 of 3 treatments: 1) no transport and full access to feed and water (CON); 2) continuous road transport for 1,290 km (TRANS), or 3) road transport for 1,290 km, with rest stops every 430 km (STOP; total of 2 rest stops). Treatments were applied from d 0 to 1 of the experiment. Cattle from TRANS and STOP treatments were transported in separate commercial livestock trailers, within a single 2.1 x 7.2 m compartment, but through the exact same route. During each rest stop, STOP cattle were unloaded and offered mixed alfalfa-grass hay and water for ad libitum consumption for 2 h. Upon arrival of STOP and TRANS on d 1, cattle were ranked by sex and BW within each treatment and assigned to 21 feedlot pens (7 pens/treatment; 2 steers and 1 heifer/pen). Full BW was recorded before (d -1 and 0) treatment application and at the end of experiment (d 28 and 29). Total DMI was evaluated daily from d 1 to 28. Blood samples were collected on d 0 (before loading of TRANS and STOP cattle), 1 (immediately after unloading of TRANS and STOP cattle), 4, 7, 10, 14, 21, and 28. Body weight shrink from d 0 to d 1 was reduced (P < 0.01) in CON compared to TRANS and STOP, and reduced in STOP compared to TRANS. Mean ADG was greater (P < 0.05) in CON compared to TRANS and STOP, but similar (P = 0.68) between TRANS and STOP. No treatment effects were detected (P >= 0.18) on hay, concentrate, and total DMI. Mean G: F was greater (P = 0.05) in CON compared to STOP, tended to be greater (P = 0.08) in CON compared to TRANS, and similar (P = 0.85) between TRANS and STOP. Plasma cortisol concentrations were greater (P <= 0.04) in TRANS compared to CON and STOP on d 1, and greater (P = 0.04) in TRANS compared to CON on d 4. Serum NEFA concentrations were greater (P < 0.01) in TRANS compared to CON and STOP on d 1, and greater (P <= 0.05) in TRANS compared to CON on d 4 and 7. Mean plasma ceruloplasmin concentrations were similar (P = 0.19) among treatments. Plasma haptoglobin concentrations were greater (P <= 0.04) in TRANS compared to CON and STOP on d 1, and in STOP compared to CON on d 1. In conclusion, inclusion of rest stops during a 1,290-km transport prevented the increase in circulating cortisol and alleviated the NEFA and haptoglobin response elicited by transport, but did not improve feedlot receiving performance of transported cattle.
Keywords: acute-phase proteins; beef cattle; feedlot receiving; rest stop; transport